A Framework for Science Exploration: Examining Successes and Challenges for Preservice Teachers - Croce, Keri-Anne (Innovations in Science Teacher Education, 2020)
Undergraduate preservice teachers examined the Science Texts Analysis Model during a university course. The Science Texts Analysis Model is designed to support teachers as they help students prepare to engage with the arguments in science texts. The preservice teachers received instruction during class time on campus before employing the model when teaching science to elementary and middle school students in Baltimore city. This article describes how the preservice teachers applied their knowledge of the Science Texts Analysis Model within this real world context. Preservice teachers’ reactions to the methodology are examined in order to provide recommendations for future college courses.